(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Today, new technologies (digital, telecommunications, biometric) are restructuring the financial services industry, actively displacing traditional players and traditional business models. Integration of new financial solutions allows to change the structure of consumption, reduce the cost of certain functionality (processing customer bases, loyalty programs, etc.), increase the efficiency and quality of business processes (target audience targeting, scoring, etc.), and significantly affect sustainability development of core business, etc. As a result, the financial technology industry (or Fintech) is gradually becoming an independent intensively developing sector. The article considers the definition of "Fintech" in foreign and domestic scientific literature. At the same time, the global directions of Fintech in Ukraine are systematized and the largest investment agreements in the field of Fintech in 2020 are determined. The financial market has undergone drastic changes over the last decade. During this time, it has transformed from a model of traditional corporate business to entire ecosystems of the banking and non-banking markets. Transformations are also dictated by new challenges that stimulate the active growth of digital operations and shape the demand for digital products and services in the financial sector. Thus, for a long time, banks have been growing due to the offer of traditional relevant products. For example, customers with current accounts were offered credit cards, personal credit lines, home loans, and so on. Later, under the influence of changing customer needs and technology development, banks began to offer related products, going beyond corporate business. Namely, they offered account management, factoring, accounting services, liquidity analysis for small and medium-sized businesses (Idea Bank, ING). At the same time, Fintech startups began launching mobile account management applications (Moven). Some financial institutions went further in non-banking offerings, providing mobile services (Post Bank), and some cooperated with health care providers and health insurance companies, providing customers with platforms with convenient payment for medical services. By expanding the boundaries of business, traditional players have begun to form value partnerships in related industries, creating ecosystems with additional benefits for customers. Partnership with fintechs and digital giants (bigtech) within the creation of such ecosystems has opened up new opportunities for traditional businesses, customers and fintech technicians themselves. With such rapid development of Fintech in the financial market, it is important to explore the main drivers and barriers to the growth of the Fintech industry in the world.